Penerapan Hukum Adat Dalam Menyelesaikan Tindak Pidana Perzinaan di Desa Teratak Kecamatan Rumbio Jaya Kabupaten Kampar - HAMDANI HAMDANI; Erdianto Effendi; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Indonesia is a rule of law where every provision is guided by a nationallegal system, the enactment of national law in society and also the development ofa legal system that derives from the habits in society. This practice is a provisioncalled customary law. In customary law there is no separation between violationsin the field of criminal or civil law. However, customary law only recognizes oneprocedure in terms of prosecution, both for civil and criminal nature.As for the settlement of cases or disputes within the customary lawcommunity, it must be based on the views or role models adopted by theindigenous people themselves. Whereas in this study shows that the settlement ofcustomary law takes into account the process in a family, deliberation betweenthe two parties and prioritizes the restoration of the order of life in the communityso that the creation of harmony within the community itself.Basically, crime is an act that is seen as a deviant act. Completion ofcriminal cases, In addition to completing it before a court, in the Tratak Villagecommunity, there are many cases of crimes that are resolved through customarylaw.This study aims to find out the existence of customary law and sanctionsagainst criminal law offenders and whether the type of sanction is effective as alegal basis in resolving this case.Keywords: State of Law, Customary Law, Customary Sanctions